2015
DOI: 10.1007/s10549-015-3480-6
|View full text |Cite
|
Sign up to set email alerts
|

The predictive and prognostic role of phosphatase phosphoinositol-3 (PI3) kinase (PIK3CA) mutation in HER2-positive breast cancer receiving HER2-targeted therapy: a meta-analysis

Abstract: The association between PIK3CA mutation and resistance to anti-HER2 therapy (AHT) is not precisely defined. This meta-analysis intended to explore the clinical utility of PIK3CA mutation in HER2-positive breast cancer treated with AHT. Literature search identified 19 eligible studies. There were 1720 patients with advanced, 828 with early and 1290 patients treated in the neoadjuvant setting. In metastatic breast cancer, AHT showed no differential objective response benefit between the wild type (WT) and the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 37 publications
3
29
1
Order By: Relevance
“…There are conflicting reports in the literature about the prognostic value of PIK3CA mutations in solid tumors. While a number of studies have suggested that the presence of a PIK3CA mutation confers a poor prognosis in several cancers including breast, lung and colorectal [30][31][32], other studies have reported no significant difference between patients harbouring PIK3CA mutations and those with wildtype PIK3CA in their tumors [33][34][35], which is consistent with our findings. However, there are currently several ongoing trials targeting PIK3CA mutated tumors with PI3K inhibitors, with some promising results.…”
Section: Discussionsupporting
confidence: 92%
“…There are conflicting reports in the literature about the prognostic value of PIK3CA mutations in solid tumors. While a number of studies have suggested that the presence of a PIK3CA mutation confers a poor prognosis in several cancers including breast, lung and colorectal [30][31][32], other studies have reported no significant difference between patients harbouring PIK3CA mutations and those with wildtype PIK3CA in their tumors [33][34][35], which is consistent with our findings. However, there are currently several ongoing trials targeting PIK3CA mutated tumors with PI3K inhibitors, with some promising results.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies in both the metastatic7880 and neoadjuvant8183 settings appear to be in the same line of the findings from preclinical experiments. However, the available data in the adjuvant setting did not show any predictive role for PIK3CA or PTEN 8487…”
Section: Conclusion and Future Perspectivessupporting
confidence: 65%
“…play an important role in mechanisms leading to this resistance (Ahmad et al, 2014). Thus, the aim of the present study was to screen CTC for mutations in the PIK3CA gene as one of previously identified resistance mechanisms (Ibrahim et al, 2015;Wilks, 2015). In blood samples from 15 out of 179 CTC-positive patients (8.4%) at least one CTC with strong HER2 expression was detected, but no patient with exclusively HER2-strongly positive CTC could be identified.…”
Section: Patient-idmentioning
confidence: 94%
“…It is important to note that overcoming resistance against HER2-targeted therapy that is frequently observed during the course of treatment has become a major challenge in tumor research (Ibrahim et al, 2015;Rexer and Arteaga, 2012;Wilks, 2015). To date, there is no routine biomarker available to predict resistance to HER2-targeted therapies and to help therapy decision making when resistance occurs.…”
Section: Introductionmentioning
confidence: 99%